The role of the chief executive - Lines, James (London : Business Books, 1978)
This book is intended for those who are responsible for the management of an autonomous business or who think that they will be in such position in the course of their career
Includes index.
gp. 23/01/2019
Loans
Keywords: Executives - roles; Leadership; Management style